Kinetics of oil-cracking for different types of marine oils from Tahe Oilfield, Tarim Basin, NW China - Anlai Ma (Journal of Natural Gas Geoscience, 2016)
The C1–C5 gas and carbon isotope ratios generated during the cracking of heavy, normal and high-waxy marine oils from Tahe Oilfield, Tarim Basin, NW China, using a closed-gold tube system under high pressure were presented. The three types of oil tested resulted in a similar gas-generation process. The C2–C5 range initially increased its yield with the application of pyrolysis temperature and thereafter decreased, while the C1 yield increased with the same application. High-waxy oil had the highest C1–C5 yield of 510 mg/goil, whereas heavy oil had the lowest C1–C5 yield of 316 mg/goil. The δ13C1 value was low at first, but gradually became higher as the pyrolysis temperature increased. However, the δ13C2 and δ13C3 values gradually became higher when the temperature was greater than 420 °C. The kinetic parameters of the C1–C5 gas generation for the different types of marine oils were then calculated using KINETIC software. This calculation resulted in a frequency factor of about 1.78 × 1014 s−1, while the distribution of the activation energy of the C1–C5 gas mass generated was relatively narrow with a range from 56 to 66 kcal/mol. Among the three types of oil tested, heavy oil had the widest activation energy distribution and the lowest major frequency of activation energy. The maximum temperature at which oil could be preserved as a separate oil phase varied from about 178 °C at a slow geological heating rate to 206 °C at a fast geological heating rate. This result is based on the kinetic parameters determined and in combination with the fractional conversion (C) of oil to gas. Testing conducted at the volatile Middle Cambrian reservoir of well Zhongshen 1 in the Tazhong Uplift strongly supported this conclusion.